Analysis Of Factors Affecting Purchase Decisions At Kopi Janji Jiwa Bengkulu - Rivaldo Dwi Ardiansyah; Neri Susanti; Dewi Harwini (Jurnal Pakar Manajemen, 2026)
This study examines the factors influencing purchasing decisions at Kopi Janji Jiwa Bengkulu. The background is the significant development of the contemporary coffee industry and the high interest of the younger generation in coffee as part of a lifestyle. The study focuses on the variables of product quality, price, promotion, and service as factors suspected to influence purchasing decisions. This study aims to identify and analyze the partial and simultaneous influence of these four variables on consumer purchasing decisions at Kopi Janji Jiwa Bengkulu. The study used a quantitative method with a survey approach and data collection through a questionnaire with a Likert scale. The study population was Kopi Janji Jiwa consumers in Bengkulu with a sample of 100 respondents taken by purposive sampling. Data were analyzed using multiple linear regression with the help of SPSS version 26 to test the influence of product quality, price, promotion, and service variables on purchasing decisions. Product quality has a significant positive effect on purchasing decisions with a regression coefficient of 0.122 and a significance of 0.050. Consumers are more likely to buy coffee products with good quality including performance, taste durability, complete features, and reliability. Price has a significant negative effect (coefficient -0.377, p = 0.003). Promotion has a significant positive effect (coefficient 0.493, p=0.000). Service also has a significant positive effect (coefficient 0.496, p=0.000). Simultaneously, these four variables significantly influence purchasing decisions with a calculated F value of 108.064 (p=0.000) and a determination coefficient R² of 0.812, meaning that 81.2% of the variation in purchasing decisions can be explained by these factors.